Chipless RFID reader architecture - Karmakar, Nemai Chandra; Koswatta, Randika; Kalansuriya, Prasanna; E-Azim, Rubayet (Artech House, 2013)
In the era of information communication technology (ICT), radio frequency identification (RFID) has been going through tremendous development. RFID technology has the potential of replacing barcodes due to its large information carrying capacity, flexibility in operations, and applications. This book addresses the new reader architecture, presents fundamentals of chipless RFID systems, and covers protocols.